MUSLIM SCHOLARS AND CHALLENGES OF SOCIAL MEDIA DA’WAH: CYBERBULLYING IN PERSPECTIVE - Muhammad Maga Sule; Salihi Ashiru Musa (Akademika, 2023)
Modern communication technology has advanced quickly, changing how social media channels are utilized for communication globally. This article focuses on Muslim scholars and the challenges of social media Da'wah focusing on cyberbullying of scholars on social media platforms. Most social media-based social interaction tools are user-generated, in contrast to traditional media. It enables the user to control the message's content without restriction or regulation. Some Muslims have been lured into using social media in violation of rules laid down by fundamental Islamic teachings because of their freedom to sign up for an account on any website and the freedom it involves. Accordingly, this study has identified cyberbullying behavior against Muslim scholars on social media and provided solutions according to Islamic teachings. Therefore, this paper aims to bring into the limelight some of the challenges Muslim scholars face when doing Da'wah on social media and proffer Islamic solutions. The study used a qualitative survey approach, interviewing seasoned social media users. Seven individuals were purposefully chosen for the study since they are Muslims and have knowledge of the issue under investigation. Some of the study's findings showed that Muslim scholars encounter cyberbullying difficulties when conducting Da'wah on social media. The paper concludes that in order to create a more peaceful and safer digital environment, social media users should communicate with good morals and manners, especially on online forums